2020
DOI: 10.1007/s13137-020-00158-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity-controlled uncertain optimization of pump-and-treat systems explained through geological entropy

Abstract: Pump-and-treat (P&T) is a widely-adopted solution for the containment of solute plumes in contaminated aquifers. A cost-effective design of P&T systems requires optimizing (minimizing) the overall pumping rates (𝑄) . This optimization is a stochastic process, as Q is a random variable linked to the randomness of the aquifer hydraulic conductivity (𝐾).Previously presented stochastic approaches to minimize 𝑄 adopted two-dimensional (2D) Gaussian random spatial fields (r.s.f.) of log-transformed K. Recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Ultimately, it is noted that the developed model could be easily extended to address cost-based optimization of the P&T system, for instance when MODFLOW and MT3DMS are coupled to cost-based optimization algorithms [59]. The water treatment costs are possibly the most critical operative issue when running P&T systems [26,28,29]. Our results indicated that higher pumping rates may reduce the contaminant mass that can be released from polluted sources with time by keeping the water table below the identified contaminant sources.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Ultimately, it is noted that the developed model could be easily extended to address cost-based optimization of the P&T system, for instance when MODFLOW and MT3DMS are coupled to cost-based optimization algorithms [59]. The water treatment costs are possibly the most critical operative issue when running P&T systems [26,28,29]. Our results indicated that higher pumping rates may reduce the contaminant mass that can be released from polluted sources with time by keeping the water table below the identified contaminant sources.…”
Section: Discussionmentioning
confidence: 89%
“…High concentrations of this compound were observed again in 2017, prompting the local administrations to take actions, such as redesigning the P&T system to properly confine the contaminant source. It was recommended that such actions were assisted by numerical modeling, which is usually developed for the design and cost-effective management of P&T systems [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the total volume of water needed to be extracted was calculated by means of Equation (8) ( Table 7). Knowing the extension of the polluted area, the hydraulic conductivity of the aquifer (Table 2), and the hydraulic gradients, both the groundwater flow rates and the remediation times were evaluated by means of Equations (11) and (12) for the cases with (Model D2) and without (Model D1) the P&T system ( Table 7).…”
Section: Batch Flushing and Adr Modelsmentioning
confidence: 99%
“…Such systems act as a hydraulic barrier for groundwater flow, avoiding the spreading of contamination outside the contaminated site boundaries (often considered as a constraint), while helping the aquifer remediation. Thanks to their versatility [8][9][10][11][12], many P&T applications can be found in Italy and worldwide. For instance, in many Italian SIN, more than one active hydraulic barrier operates.…”
Section: Introductionmentioning
confidence: 99%
“…Connectivity, clustering and spatial ordering can be measured in multiple manners, e.g. through the analysis of geological entropy Pedretti 2018, 2017;Pedretti 2020;Pedretti and Bianchi 2019;Ye et al 2018). However, connectivity is not yet an established aspect for waste rock modeling.…”
Section: Connectivity and Spatial Ordermentioning
confidence: 99%